Follicle-Stimulating Hormone (FSH) and Luteinizing Hormone (LH) in the Urine of Prepubertal Children - Rifkind, Arleen B. (1967)
Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) have been measured by specific bioassays in pooled urine samples from prepubertal children, aged 2-6 yr, and from male adults. For children the mean urinary excretion of FSH was 2.2 U 2nd International Reference Preparation (2nd IRP) per liter and the mean urinary excretion of LH was 0.44 U 2nd IRP per liter. For adults the mean FSH excretion was 5.6 U 2nd IRP per liter and the mean LH excretion was 4.7 U 2nd IRP per liter. Our data show a 2.5-fold increase of FSH, a 10.7-fold increase of LH, and a consequent decrease in the FSH: LH ratio from 5 to 1 between childhood and adulthood. FSH and LH in urine from three patients with gonadal abnormalities have also been studied. The results from normal children, adults, and abnormal patients form a spectrum and reveal that sexual maturity is accompanied by a marked increase in the excretion of LH with relatively smaller increases in FSH.